Estimation of Population Dynamics Parameters of Selar crumenophthalmus Landed at Gorontalo Tenda Fish Landing Base: Pendugaan Parameter Dinamika Populasi Ikan Selar crumenophthalmus yang Didaratkan di Pangkalan Pendaratan Ikan Tenda Gorontalo - Nuralim Pasisingi; Ogyn Sutanto Mokoagow; Faizal Kasim (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2024)
This research aimed to determine the age group, growth, mortality, and yield per recruitment (Y/R) of Selar crumenophthalmus landed at Gorontalo City Tenda Fish Landing Base. A total of 1020 samples were collected randomly from fishermen who landed their catches at Tenda Fish Landing Base. The results of research based on sampling carried out twice a week from March to May 2023 showed that there were three age groups of S. crumenophthalmus. The percentages for age groups I, II, and III were 39.90%, 55.30%, and 4.30%, respectively. The asymptote length of the fish L∞ = 269.4 mm, the growth rate of the fish K = 0.55 and the theoretical age of the fish t0 = -0.1616 years. The natural mortality M = 0.48 was smaller than fishing mortality F = 0.85, total mortality Z = 1.33 per year, and total exploitation rate E = 0.64 per year. The Y/R value was 0.106 grams/recruitment with an exploitation rate of 0.608 per year.